2020
DOI: 10.3386/w27673
|View full text |Cite
|
Sign up to set email alerts
|

The 1918 Influenza Pandemic and its Lessons for COVID-19

Abstract: The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 101 publications
(59 reference statements)
2
42
0
3
Order By: Relevance
“…11 See Stern et al (2009) for a list of NPIs by type and city. For greater discussion of the many papers related to the 1918 pandemic, see the recent surveys by Arthi and Parman (2020) and Beach et al (2020). In addition, Almond (2006), Almond and Currie (2011), Almond et al (2018), andBeach et al (2018) provide detailed surveys of the long-run e ects of early childhood exposure to health shocks, including in uenza.…”
Section: School Closuresmentioning
confidence: 99%
See 1 more Smart Citation
“…11 See Stern et al (2009) for a list of NPIs by type and city. For greater discussion of the many papers related to the 1918 pandemic, see the recent surveys by Arthi and Parman (2020) and Beach et al (2020). In addition, Almond (2006), Almond and Currie (2011), Almond et al (2018), andBeach et al (2018) provide detailed surveys of the long-run e ects of early childhood exposure to health shocks, including in uenza.…”
Section: School Closuresmentioning
confidence: 99%
“…Besides Camp Funston, other military camps throughout the country recorded severe outbreaks during March and April 1918(Crosby, 2003, p.19).9 An excellent description of the in uenza pandemic in 50 large U.S. cities is provided in Navarro and Markel's digital In uenza Encyclopedia; see http://www.in uenzaarchive.org/about.html.10 Clay et al (2018) show that air pollution (measured by the intensity of burning coal) elevated mortality rates in U.S. cities during the pandemic. Other factors such as distance to military camps, di erences in pre-pandemic mortality, poverty rates and the population composition also contributed to the uneven distribution of the pandemic severity across the country(Crosby, 2003;Beach et al, 2020).…”
mentioning
confidence: 99%
“…COVID-19 is perceived as a local virus infection emanated from China, which rapidly spread across the world and turned into a pandemic. The 1918 influenza pandemic, also known as the Spanish flu, which had resulted in an estimated 20 million death toll due to respiratory infections, is the closest parallel to the COVID-19 (Beach, Clay & Saavedra, 2020). Besides, resulting in the short-term scarcity of labor, the spiraling costs of production, duress on public resources and social security systems, pandemics also have a long-term "hysteresis" effect in terms of a permanent loss of a potential output…”
Section: Introductionmentioning
confidence: 99%
“…Using a differences‐in‐differences approach, they found that lives lost to natural causes (i.e., non‐COVID related such as septicemia, pneumonia, and diabetes) and to COVID‐19 fell by 15 per 100,000 residents on a weekly basis. Given that the cumulative number of deaths in pandemics is related to the extent of economic contractions (Barro et al ., 2020; Beach et al ., 2020; Geloso and Bologna Pavlik, 2020), their results suggest that CON laws might have seeped through to economic activity on a more macro‐level. Taking the sum of all similar interventions that limit the ability of businesses to adjust, and that is a large sum, suggests that governments can deepen economic shocks.…”
Section: Institutions Economic Freedom and Robustnessmentioning
confidence: 93%